Impact of age and gender on glioblastoma onset, progression, and management - Colopi, Ambra; Fuda, Serena; Santi, Samuele; Onorato, Angelo; Cesarini, Valeriana; Salvati, Maurizio; Balistreri, Carmela Rita; Dolci, Susanna; Guida, Eugenia (Mechanisms of ageing and development, 2023)
Glioblastoma (GBM) is the most common primary malignant brain tumor in adults, while its frequency in pediatric patients is 10–15%. For this reason, age is considered one of the major risk factors for the development of GBM, as it correlates with cellular aging phenomena involving glial cells and favoring the process of tumor transformation. Gender differences have been also identified, as the incidence of GBM is higher in males than in females, coupled with a worse outcome. In this review, we analyze age- and gender- dependent differences in GBM onset, mutational landscape, clinical manifestations, and survival, according to the literature of the last 20 years, focusing on the major risk factors involved in tumor development and on the mutations and gene alterations most frequently found in adult vs young patients and in males vs females. We then highlight the impact of age and gender on clinical manifestations and tumor localization and their involvement in the time of diagnosis and in determining the tumor prognostic value. •Glioblastoma is the most common primary malignant brain tumor in adults.•The incidence of glioblastoma is higher in males than in females•Chemotherapy is more effective in adult compared to pediatric patients